Domestic determinants of foreign policy making in post-Suharto Indonesia - Mushoffa, Eva (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2009)
This study investigates domestic sources of Indonesia’s foreign policy under three democratically elected presidents: Abdurrahman Wahid (1999-2001), Megawati Sukarnoputri (2001-2004) and Susilo Bambang Yudhoyono (2004-2009). The study uses documentary analytical method of data collection. The study suggests that postSuharto administrations promoted preservation of Indonesia’s territorial integrity and attempted to get financial assistance needed for development of the country. The study has also found out that foreign policy making has become an object of intense debate between the executive, the presidential council, the bureaucracy, the parliament and the public at large. Hence, the traditional role of the military in foreign policy making has declined. However, the degree of influence of these sources of foreign policy is dependent on the nature of the issue and the personalities heading these institutions. The study, among others, recommends that the democratization of Indonesian society should continue unabated as Indonesian democracy has yet to become mature.